Pelatihan Penulisan Sejarah Lokal Pada Siswa Di Kabupaten Majene - Subair, Ahmad; Syahrul, Syahrul; Patahuddin, Patahuddin (Journal of Community Sustainability, 2024)
One of the main problems often faced by students is that not all students understand how important it is to write local history. Students also lack an understanding of the appropriate principles and techniques for writing local history at the schools where they work. Apart from that, students sometimes have a tendency to be less motivated to write history that is regionally based or familiar with local history. From the description above, it can be seen that it is important to provide local history writing training for history students in Majene district, West Sulawesi province. In the midst of limited time, funds and energy, local history writing training can be provided to students throughout Majene Regency. The Community Service Team decided that a program needed to be created to provide assistance in the form of local history writing training for history in Majene Regency. This training will focus on increasing motivation, understanding and ability to implement local history writing. After training, it is hoped that students will be able to solve problems with historical writing because they are already proficient in using it.